BIMBINGAN TEKNIS PENANGANAN PASCA PANEN DAN TRANSPORTASI LOBSTER PASIR (Panulirus homarus) DI KERAMBA JARING APUNG DUSUN UJUNG BETOK LOMBOK TIMUR - Asri, Yuliana; Affandi, Rangga Idris; Mulyani, Laily Fitriani; Dwiyanti, Septiana; Rahmadani, Thoy Batun Citra; Alim, Sahrul; Diniariwisan, Damai; Setyono, Bagus Dwi Hari; Sumsanto, Muhammad (Universitas Mataram, 2025)
Spiny lobsters (Panulirus homarus) are a high-value fishery commodity with strong demand in both local and international markets. Ujung Betok, located on the coast of East Lombok, is a center for spiny lobster aquaculture using floating net cages (FNC). Despite growing production, a common issue observed during transport is the decline in lobster quality, and in some cases, mortality, which significantly reduces market value. To address this problem, technical training was conducted focusing on post-harvest handling and transportation techniques aimed at preserving lobster quality up to the point of delivery. The activity was carried out through field surveys, educational sessions, and hands-on practical demonstrations at the FNC sites in Ujung Betok. Effective post-harvest handling is indicated by the lobster's ability to survive transport in healthy, undamaged condition, maintaining freshness equivalent to that at harvest. The post-harvest procedure includes sorting, holding, cold stunning, packaging, and transportation. Drier packaging methods have shown to significantly extend survival during transit. The fundamental principle of spiny lobster handling and packaging is to maintain product quality while minimizing physical injury and stress, both of which can lead to mortality.